Dystonia type 28 with early onset (DYT-KMT2B): a clinical case - V. A. Bulanova; M. A. Bykanova; N. А. Kuleva (Русский журнал детской неврологии, 2022)
This article presents a clinical observation of a patient with a rare form of primary dystonia – type 28 dystonia associated with a heterozygous mutation in the KMT2B gene (OMIM: 617284) for the first time in the Russian literature. The disease started at the age of 6 years with unilateral dystonia of the foot, acquired the features of generalized dystonia in the 1st year from the beginning. The mutation found in proband (chr19:36229249GC>G) was not described earlier. Dystonia was insensitive to levodopa, the effect of botulinum toxin treatment was insufficient; a notable clinical result has been achieved with deep brain stimulation (DBS).